Taxonomic revision of the king cobra Ophiophagus hannah (Cantor, 1836) species complex (Reptilia: Serpentes : Elapidae), with the description of two new species - Indraneil, Das; P. Gowri, Shankar; Priyanka, Swamy; Rhiannon C., Williams; Hmar Tlawmte, LALREMSANGA; P., PRASHANTH; Gunanidhi, Sahoo; S.P., Vijayakumar; Jacob, Hoglund; Kartik, Shanker; Sushil K., Dutta; S.R., Ganesh; et al. (EJT Consortium, 2024)
The taxonomy of king cobras (Ophiophagus) was reevaluated using qualitative, mensural and meristic characters, based on 148 entire and five skeletal specimens, and supported by a recent molecular phylogenetic analysis. We provide nomenclatural synopses of both the genus and species- series nomina. We restrict the concept of Ophiophagus hannah s. str. to populations from eastern Pakistan, northern and eastern India, the Andaman Islands, Indo-Burma and Indo-China, south to central Thailand. The nomen Ophiophagus bungarus (Schlegel, 1837) comb. nov. is revived for the populations inhabiting the Sunda Shelf area, including the Malay Peninsula, the Greater Sunda Islands and parts of the southern Philippines. We describe two new species, Ophiophagus kaalinga Gowri Shankar, Das & Ganesh sp. nov. endemic to the Western Ghats of south-western India and Ophiophagus salvatana Gowri Shankar, Das & Wüster sp. nov., inhabiting the island of Luzon in northern Philippines. For the purpose of nomenclatural stability, we designate a neotype for Hamadryas hannah Cantor, 1836. A dichotomous identification key to the four species recognized here is provided.